1996
DOI: 10.1002/jbmr.5650110112
|View full text |Cite
|
Sign up to set email alerts
|

Expression of osteocalcin in the patella of experimentally immobilized and remobilized rats

Abstract: The exact mechanisms by which mechanical loading-unloading affects bone tissue are mostly unknown. Recently, osteocalcin, a direct product of osteoblasts, has been shown to reflect the activity of the mineralization phase of the newly formed bone matrix, and therefore, the in situ detection of osteocalcin could be used for studying the effects of physical activity-inactivity on the osteoblast function or bone formation in the target bone. In this study, the effect of various loading states (immobilization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Retrocalcaneal enthesophytes may be an adaptive response to increased traction in the Achilles tendon [2021]. Increased mechanical loading triggers osteoblastic activity at the tendon attachment site, and physically active people are more likely to exhibit presence of enthesophytes [2223]. Thus, presence of retrocalcaneal enthesophyte may imply that the patient has high activity level and is more liable to overuse injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Retrocalcaneal enthesophytes may be an adaptive response to increased traction in the Achilles tendon [2021]. Increased mechanical loading triggers osteoblastic activity at the tendon attachment site, and physically active people are more likely to exhibit presence of enthesophytes [2223]. Thus, presence of retrocalcaneal enthesophyte may imply that the patient has high activity level and is more liable to overuse injuries.…”
Section: Discussionmentioning
confidence: 99%
“…12,17 To date, Deymier et al (2020) 6 is the only study to have investigated the effects of spaceflight on entheses. Whereas studies have demonstrated that entheses are sensitive to chronic variations in mechanical load, [18][19][20][21][22][23] Deymier et al (2020) 6 reported that spaceflight did not mechanically weaken the supraspinatus tendon enthesis. However, the supraspinatus, a shoulder muscle, is documented as suffering little impact from microgravity.…”
Section: Introductionmentioning
confidence: 99%
“…Osteocalcin is an important protein associated with bone formation and its levels in serum directly correlate with measurements of bone mineral density [59] , [60] . Osteocalcin expression is increased in response mechanical loading in both in vivo and in vitro models [61] , [62] . We also analyzed expression of cyclooxygenase-2, runx2, osterix, and osteopontin and found inhibition of Src had no impact on OFSS-induced increases in their expression (data not shown).…”
Section: Discussionmentioning
confidence: 99%